Design of navigation light using Microcontroller - Muhammad Irfanius; Basrah Pulungan, Ali (Department of Electrical Engineering Universitas Negeri Padang, 2025)
This final project discusses the design and development of a icrocontroller-based navigation light system. This system aims to improve maritime safety by providing a more accurate and comprehensive control and monitoring system for navigation light conditions. The system uses an Arduino Mega 2560 microcontroller as the main controller, equipped with current and voltage sensors to monitor lamp condition parameters periodically. Manual control of the navigation lights is done via pushbuttons, and information about the lamp conditions (voltage and current) is displayed on an LCD screen. In addition, the system is equipped with a buzzer as an early warning alarm if abnormal conditions are detected in the lamp, such as voltage or current exceeding normal limits. It is hoped that this system can provide a solution to maritime safety problems by providing more complete and accurate information regarding the condition of navigation lights, as well as enabling more effective preventative actions